Emerging roles and context of circular RNAs. (9th September 2016) - Panda, Amaresh C.; Grammatikakis, Ioannis; Munk, Rachel; Gorospe, Myriam; Abdelmohsen, Kotb
Abstract : Circular RNAs (circRNAs) represent a large class of noncoding RNAs (ncRNAs) that have recently emerged as regulators of gene expression. They have been shown to suppress microRNAs, thereby increasing the translation and stability of the targets of such microRNAs. In this review, we discuss the emerging functions of circRNAs, including RNA transcription, splicing, turnover, and translation. We also discuss other possible facets of circRNAs that can influence their function depending on the cell context, such as circRNA abundance, subcellular localization, interacting partners (RNA, DNA, and proteins), dynamic changes in interactions following stimulation, and potential circRNA translation. The ensuing changes in gene expression patterns elicited by circRNAs are proposed to drive key cellular processes, such as cell proliferation, differentiation, and survival, that govern health and disease. WIREs RNA 2017, 8:e1386. doi: 10.1002/wrna.1386 This article is categorized under: RNA-Based Catalysis > RNA Catalysis in Splicing and Translation RNA Interactions with Proteins and Other Molecules > Protein–RNA Interactions: Functional Implications Regulatory RNAs/RNAi/Riboswitches > Regulatory RNAs Abstract :